Extraction of pure transfer probabilities from experimental transfer and capture data - Scamps G. Guillaume; Sargsyan V. V. Vagit Vagitovich; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Lacroix D. (2016, 2016)
Title screen